THE IMPLEMENTATION OF TEACHING FACTORY THROUGH DEPARTMENT DIVISION IN HOSPITALITY SKILL PROGRAMME AT METLAND TOURISM VOCATIONAL SCHOOL - Darmawan Sunarja; Ony Dina Maharani (Lembaga Pengembangan Pembelajaran Penelitian dan Pengabdian Masyarakat Universitas PGRI Mahadewa Indonesia, 2023)
This study aims to determine the implementation of Teaching Factory at the Metland Tourism Vocational School. The teaching factory is implemented through the division of students into 4 departments in 7 activities in the hospitality skills program. Based on the research that has been done, the results show that the ability of students in Front Office activities is 92.7% in the very good category, Food and Beverage is 97.8% in the very good category, Sales is 99.4% in the very good category, Kitchen Knowledge is 96.4% in the very good category, Bar is 88.8% in the very good category, Housekeeping is 96% in the very good category, and Laundry is 96.8% in the very good category. Meanwhile, for soft skills, the results of moral knowledge were 96.1%, with very good categories, moral feelings were 97% in very good categories, and moral actions were 97.6% in very good categories. This shows that the application of teaching factory through dividing students into 4 departments in 7 activities can improve soft skills and hard skills. The type of research used is a case study with a qualitative approach.